Dwie tradycje badawcze w językoznawstwie stosowanym dotyczącym języka drugiego - Niżegorodcew, Anna (Neofilolog, 2009)
The present paper presents two theoretical and research traditions concerning second language acquisition and use: psycholinguistic and sociocultural ones. It provides a historical overview of the field of psycholinguistics and second language acquisition studies since the 1950s with its more recent critique from the representatives of the sociocultural developments in second language theory. The quantitative and qualitative research approaches in contemporary L2 applied linguistics studies are illustrated with a recent study of the acculturation process of Polish immigrants in the United Kingdom done by an MA student.